TINJAUAN HUKUM ISLAM TERHADAP YOUTUBE SEBAGAI SUMBER PENGHASILAN(Studi Kasus Youtuber dari Civitas Ma’had Al-Zaytun) - Usmaniah, Nur; Iswandi, Irvan; Fitri, Ahmad Asrof (Journal of Islamic Studies, 2023)
Youtube is a video sharing website where users can upload, watch and share videos with other users. Youtube can not only be used to seek entertainment, seek information and knowledge, but can also be used as a business medium to make money. The purpose of this research is to find out and understand how the Youtube process can be used as a source of income and how Islamic law reviews Youtube as a source of income. This study used field research and using observation research methods and semi-structured interviews. The sampling method used is Nonprobability Sampling. In this study, researchers used a purposive sampling technique. The result of this study indicate that: 1) At the time of monetization, we are given the choice to determine the type of source of income we want to get from YouTube. A YouTube accout can already earn income if it has been monetized by Google and meets the minimum number of subscribers and views; 2) When viewed from the object, the form of ijarah used is charity ijarah, namely ijarah for actions or human labor which is termed wwages. Judging from the legal terms of buying and selling, one of them is the law is valid and lawful. If seen from the terms of sale and purchase, then the law is permissible.